Pengembangan E-LKPD Interaktif Berbasis Liveworksheet pada Materi Bangun Datar Kelas IV SD - Epa Sopiana; Atiaturrahmaniah Atiaturrahmaniah; Arif Rahman Hakim (Journal on Education, 2023)
This study aimed to produce interactive E-LKPD products based on live worksheets on two-dimensional figure material in grade IV SD, with the number of samples used by 20 students. The method used is Research And Development (R&D), referring to the ADDIE development model (Analyze, Design, Development, Implementation and Evaluation). Based on the research that has been done, the analysis of the material validation obtained a score of 80 with the category "Eligible", and the display expert validation obtained a score of 104 with the category "Feasible". Meanwhile, from the students’ results, Responses scored 1,075 with an average acquisition of 53.75. From the learning outcomes test using the pre-test and post-test, The pre-test results obtained a score of 1,330 with an average acquisition of 66.5, While the post-test results obtained a score of 1,540 with an average score of 77. Therefore, it can be seen previously and currently using the live worksheet-based interactive E-LKPD above. Thus, this live worksheet-based interactive E-LKPD is feasible for the learning process.